2000
DOI: 10.1128/mcb.20.11.3965-3976.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Domains and Residues within the ɛ Subunit of Eukaryotic Translation Initiation Factor 2B (eIF2Bɛ) Required for Guanine Nucleotide Exchange Reveals a Novel Activation Function Promoted by eIF2B Complex Formation

Abstract: Eukaryotic translation initiation factor 2B (eIF2B) is the guanine nucleotide exchange factor for protein synthesis initiation factor 2 (eIF2). Composed of five subunits, it converts eIF2 from a GDP-bound form to the active eIF2-GTP complex. This is a regulatory step of translation initiation. In vitro, eIF2B catalytic function can be provided by the largest (epsilon) subunit alone (eIF2B). This activity is stimulated by complex formation with the other eIF2B subunits. We have analyzed the roles of different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
124
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(134 citation statements)
references
References 46 publications
10
124
0
Order By: Relevance
“…These alleles used in Figure 5D cause significant impairment of eIF2B GEF activity and impart a slow-growth phenotype and 3AT resistance (Gomez and Pavitt, 2000) that was enhanced here by hc eIF5. Interestingly, hc eIF5 did not alter the growth rate of slow-growing strains analyzed bearing mutations in eIF2Bb (gcd2), g (gcd1), and d (gcd7) genes ( Figure 5E).…”
Section: Hc Eif5 Does Not Promote Formation Of Mfc Lacking Trna I Metmentioning
confidence: 99%
“…These alleles used in Figure 5D cause significant impairment of eIF2B GEF activity and impart a slow-growth phenotype and 3AT resistance (Gomez and Pavitt, 2000) that was enhanced here by hc eIF5. Interestingly, hc eIF5 did not alter the growth rate of slow-growing strains analyzed bearing mutations in eIF2Bb (gcd2), g (gcd1), and d (gcd7) genes ( Figure 5E).…”
Section: Hc Eif5 Does Not Promote Formation Of Mfc Lacking Trna I Metmentioning
confidence: 99%
“…The Asn-Phe Motif in eIF2B⑀ is Necessary for Activity in Human eIF2B-Gomez and Pavitt (5) showed that an Asn-Phe (NF) motif in yeast eIF2B⑀ (residues 249/250 in yeast, 263/264 in human) was important for facilitating the enhancement of eIF2B activity that results from the formation of holocomplexes. This motif is conserved in all available eIF2B⑀ sequences.…”
Section: And B)mentioning
confidence: 99%
“…eIF2B⑀ contains within its C-terminal region the catalytic domain (approximately residues 527-726 in human eIF2B⑀), which mediates GDP/GTP exchange on eIF2 (5,6) (Fig. 1A).…”
mentioning
confidence: 99%
“…This region encompasses residues 518 -583 of the yeast protein and is well conserved in all eIF2B⑀ proteins (12). In addition, mutation of either Thr 552 to Ile (T552I) or Ser 576 to Asn (S576N) directly impairs catalytic function without detectably impairing binding to eIF2 (14). Thus, although the eIF2B⑀ C terminus is only a small fragment of the entire ϳ275-295-kDa eIF2B complex, it contains the major functional regions required for nucleotide exchange and provides a structural model for the related C termini of eIF4G and eIF5.…”
mentioning
confidence: 99%